OP0026 A RANDOMIZED, CONTROLLED TRIAL OF RITUXIMAB VERSUS AZATHIOPRINE AFTER INDUCTION OF REMISSION WITH RITUXIMAB FOR PATIENTS WITH ANCA-ASSOCIATED VASCULITIS AND RELAPSING DISEASE. (2nd June 2020) - Smith, R.; Jayne, D.; Merkel, P. A.
Abstract : Background: Rituximab (RTX) is an effective therapy for induction of remission in ANCA-associated vasculitis (AAV). However, the effect of RTX is not sustained, and subsequent relapse rates are high, especially in patients with a history of relapse. Objectives: The RITAZAREM trial is an international, multi-center, open-labelled, randomized, controlled trial of patients with AAV with relapsing disease comparing the efficacy, after induction of remission with RTX, of two relapse-prevention strategies: repeat dosing of RTX or daily oral azathioprine (AZA). Methods: Patients with AAV were recruited at the time of relapse and received induction therapy with RTX and glucocorticoids. If remission was achieved by month 4, patients were randomized in a 1:1 ratio to receive either RTX (1000 mg every 4 months for 5 doses) or AZA (2 mg/kg/day) as maintenance therapy. Patients were followed for a minimum of 36 months, with the primary outcome being time to disease relapse. Results: 190 patients were enrolled and 170 randomized at 4 months (85 to RTX; 85 to AZA). The data are complete on all patients up to at least month 24. Median age was 59 years (range 19-89), with a prior disease duration of 5.3 years (0.4-38.5). 123/170 (72%) patients had a history of testing positive for anti-proteinase 3 ANCA; 47/170 (28%) for myeloperoxidase ANCA; 104/170 (61%) were enrolled having suffered a major relapse, and 48/170 (28%) received a pre-specified higher dose glucocorticoid induction regimen (Table 1 ). RTX was superior to AZA in preventing disease relapse with a preliminary overall hazard ratio (HR) estimate of 0.36 (95% CI 0.23-0.57, p <0.001) and a during-treatment HR estimate of 0.30 (95% CI 0.15-0.60, p<0.001) (Figure 1 ). After adjustment, none of the randomization stratification covariates (ANCA type, glucocorticoid induction regimen, or relapse severity) had a significant differential effect on the primary outcome. By 24 months after entry, 20 months after randomization, 11/85 (13%) patients in the RTX group had experienced a relapse compared to 32/85 (38%) patients in the AZA group. 19/85 (22%) patients in the RTX group and 31/85 (36%) patients in the AZA group experienced at least one severe adverse event (SAE). 25/85 (29%) and 42/85 (49%) patients in the RTX group developed hypogammaglobulinaemia (IgG <5g/l) and non-severe infections respectively, compared to 21/85 (25%) and 41/85 (48%) in the AZA group. Conclusion: In the RITAZAREM trial, following induction of remission with RTX, RTX was superior to AZA for preventing disease relapse in patients with AAV with a prior history of relapse. There were no new major safety signals for use of these medications in this population. Disclosure of Interests: Rona Smith Grant/research support from: Roche, David Jayne Grant/research support from: ChemoCentryx, GSK, Roche/Genentech, Sanofi-Genzyme, Consultant of: Astra-Zeneca, ChemoCentryx, GSK, InflaRx, Takeda, Insmed, Chugai, Boehringer-Ingelheim, Peter A. Merkel Grant/research support from: AstraZeneca, Bristol-Myers Squibb, Boeringher-Ingelheim, Celgene, ChemoCentryx, Genentech/Roche. Genzyme/Sanofi, GlaxoSmithKline, InflaRx, Kypha, TerumoBCT., Consultant of: AbbVie, AstraZeneca, Biogen, Bristol-Myers Squibb, Boeringher-Ingelheim, Celgene, ChemoCentryx, Genentech/Roche, Genzyme/Sanofi, GlaxoSmithKline, InflaRx, Insmed, Jannsen, Sparrow, Kiniksa.